Validation of Workplace Bullying Scale on the Bangladeshi Adults - Mollika Roy; Ummay Salma Ruma; Barun Kummer Bhattacharja (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2024)
The present study aims to adapt a workplace bullying scale in Bengali that will enable us to assess workplace bullying precisely in the Bangladeshi job sector. Previous workplace bullying studies identified two elements on the WB scale, namely work-related and person-related. In the adapted version of the WB scale, these components are conceptually comprehensible and comparable to the original scale. We have performed different psychometric analyses to adapt the WB scale to Bengali. Item analysis tests were executed using exploratory and confirmatory factor analysis. Findings from both of these tests were satisfactory for the test items. Next, we performed reliability tests using Cronbach’s alpha to assess internal and external reliability to assess inter-rater reliability. The scale demonstrates a satisfactory internal and external reliability level, indicating consistency. Finally, a convergent validity test was performed by comparing the obtained WB and well-being scale scores. The significant negative correlation between workplace bullying and well-being enables us to align the theoretical concept of the workplace bullying variable with pertinent variables, demonstrating a reasonable degree of convergent validity of the scale. This adapted WB scale has proved to be an efficient psychometric tool that appropriately measures workplace bullying in Bengali.